Virus Diversity and Loads in Crickets Reared for Feed: Implications for Husbandry - de Miranda, Joachim R.; Granberg, Fredrik; Low, Matthew; Onorati, Piero; Semberg, Emilia; Jansson, Anna; Berggren, Åsa (Frontiers in Veterinary Science, 2021)
Insects generally have high reproductive rates leading to rapid population growth and high local densities; ideal conditions for disease epidemics. The parasites and diseases that naturally regulate wild insect populations can also impact when these insects are produced commercially, on farms. While insects produced for human or animal consumption are often reared under high density conditions, very little is known about the microbes associated with these insects, particularly those with pathogenic potential. In this study we used both target-free and targeted screening approaches to explore the virome of two cricket species commonly reared for feed and food, Acheta domesticus and Gryllus bimaculatus. The target-free screening of DNA and RNA from a single A. domesticus frass sample revealed only 1% viral nucleic acids, including known cricket, insect, bacterial and plant pathogens, as well as a diverse selection of novel viruses. The targeted screening revealed relatively high levels of Acheta domesticus densovirus, invertebrate iridovirus 6 and a novel iflavirus, as well as low levels of Acheta domesticus volvovirus, in insect and frass samples from several retailers. Our findings highlight the value of multiple screening approaches for a comprehensive and robust cricket disease monitoring and management strategy. This will become particularly relevant as-and-when cricket rearing facilities scale up and transform from producing insects for animal feed to producing insects for human consumption.